Sistem Informasi Inventory Persediaan Barang Striping Motor Berbasis Web dengan Metode Prototype Pada Bengkel Ageng Motor - Fitriana, Saghifa; Wicaksono, Ageng; Nouvel, Ahmad; Kristania, Yustina Meisella (Informatics and Computer Engineering Journal, 2025)
Information technology is currently experiencing very rapid development and following progress in all fields. Technological developments change the way information is spread quickly and easily. Forming an information system requires systematic processing to meet information needs. Ageng Motor Cilacap still checks inventory manually by the business owner. Data on incoming and outgoing goods is recorded using a form made by the business owner and accompanied by a receipt showing the number of buyers' orders. As a result of this problem, errors sometimes occur in inventory calculations as well as difficulties in recording and making reports on incoming and outgoing goods. With a good information system, it is hoped that the process of managing goods entering and leaving motorbike striping can be carried out more efficiently, accurately and quickly. This certainly brings many benefits to the business world, such as increasing productivity, saving time and costs, as well as increasing customer satisfaction. This research uses the prototype method of software development. Data collection used was interviews, observation and reference studies. The results of this research are the object of research regarding the incoming and outgoing goods inventory procedures that are applied.